Development of WhatsApp for English Learning at Saumlaki State High School Tanimbar Islands - Titirloloby, Piter (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The purpose of this study was to describe how WhatApps media in teaching grammar to students and describe the issue, and action research was conducted on thirty-two second-grade students. The data were collected from a questionnaire and observation checklist to assess students' engagement and how they used WhatsApp in learning. The results indicated that in cycle one, only 22, or 66%, of the students had achieved the passing grade, while in cycle 2, 32 students, or 100%, achieved the passing grade. There was an increase of 34% in students in the second cycle. The researcher finished cycle two because the total number of the student's results was standard score minimum achievement criterion 75. The students learned better in cycle 2. The students were active and participated in learning grammar using WhatsApp as media. The WhatsApp platform had the power to increase students' instructional interaction, mainly student-student interaction, followed by student-content interaction and student-teacher interaction in the teaching and learning process directly or online using WhatsApp as media. The WhatsApp platform provides participants with an open and flexible space for communicating, expressing ideas, and exchanging information, and the critical issue is WhatsApp can help students in learning grammar.